STRATEGI DAN MODEL PEMBELAJARAN SKI - Muslih , Misbahul; Wahono , Suparwoto Sapto; Damiri, Madzkur (Tsaqofah : Jurnal Pendidikan Islam, 2023)
In the world of Islamic Religious Education, there are many subjects whose delivery is slightly delayed and will be imperfect, as is the case in the subject History of Islamic Culture. This subject is quite difficult in terms of delivery, many teachers do not deliver it optimally because the strategies used are still inadequate, they only focus on one model, namely lectures. This results in students easily getting bored because they only listen to the teacher lecture and then write and do assignments. Therefore, in the SKI learning process, efforts are made to achieve maximum learning, at least having strategies that can be used to encourage the delivery of material, because strategy is a component of learning.